Solid acid catalyst and device and method for preparing polysiloxane by using solid acid catalyst
The solid acid catalyst prepared by acid leaching and calcining treatment solves the problems of complex polydimethylsiloxane process and low effective component content in the prior art, and achieves the effect of improving the porosity of polyurethane foam and simplifying the process.
Patent Information
- Application Number
- CN202411788341.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art When preparing low molecular weight polydimethylsiloxanes, the process is complicated, it is easy to produce waste, and the effective component content is low.
The mesoporous zirconium phosphate powder after acid leaching is used for granulation and calcination, and the acid leaching is then carried out again to prepare a solid acid catalyst with good catalytic properties. This catalyst is used to prepare polysiloxanes to increase the content of the target components.
The solid acid catalyst prepared by this method can effectively increase the content of the target components in the low molecular weight polysiloxane, improve the porosity of the polyurethane foam, and simplify the process and be environmentally friendly.
Smart Images

Figure CN119390983A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organic silicon, in particular to a solid acid catalyst and a device and a method for preparing polysiloxane using the solid acid catalyst. Background Art
[0002] High-resilience polyurethane foam is widely used in mattress products, furniture cushions, car seats and other fields because of its good physical and mechanical properties and extremely high resilience. The performance of high-resilience polyurethane foam depends largely on the structure of its internal pores. Polydimethylsiloxane can affect the size, shape and distribution of pores. It can not only promote the refinement of pores and make the foam denser, thereby improving the strength and resilience of the foam; it can also adjust the size of pores and improve its air permeability.
[0003] At present, the synthesis method of low molecular weight polydimethylsiloxane is basically to use sulfuric acid, ion exchange resin and other catalysts to synthesize low molecular weight polydimethylsiloxane, but the preparation process is complicated and cumbersome, and it is easy to generate solid or liquid waste, and the content of effective components of the prepared polydimethylsiloxane is low.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a solid acid catalyst and a device and method for preparing polysiloxane using the solid acid catalyst.
[0006] The invention provides a method for preparing a solid acid catalyst, which comprises: subjecting acid-leached mesoporous zirconium phosphate powder to granulation and calcination, and then subjecting it to acid leaching again to obtain a solid acid catalyst.
[0007] The present invention also provides a device for preparing polysiloxane, which mainly comprises: a raw material tank, a reaction tank and a product tank, wherein the raw material tank is connected to the reaction tank, the reaction tank is connected to the product tank, and a catalyst placement box is arranged in the reaction tank, wherein the solid acid catalyst prepared by the above preparation method is placed in the catalyst placement box.
[0008] The present invention also provides a method for preparing polysiloxane using the above-mentioned device, comprising the following steps: adding reaction raw materials into a raw material tank, loading the prepared solid acid catalyst into a catalyst placement box and then filling it into a reaction tank, and introducing the reaction raw materials in the raw material tank into the reaction tank for reaction.
[0009] The present invention also provides a method for preparing high-resilience polyurethane foam, which comprises: preparing high-resilience polyurethane foam by compounding the polysiloxane prepared by the above preparation method with a surfactant obtained by polyether.
[0010] The present invention has the following beneficial effects:
[0011] The present invention provides a solid acid catalyst and a device and method for preparing polysiloxane using the solid acid catalyst. The preparation method of the solid acid catalyst provided by the present invention comprises: subjecting the mesoporous zirconium phosphate powder after acid leaching to granulation treatment and roasting treatment, and then subjecting it to acid leaching treatment again to prepare the solid acid catalyst. The solid acid catalyst prepared by the above method has good catalytic performance. The solid acid catalyst is used to prepare polysiloxane, which can effectively increase the content of the target component. The prepared low molecular weight polysiloxane and polyether are compounded as surfactants to prepare polyurethane foam, which can effectively increase the open cell rate of high resilience foam. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0013] Figure 1 The device for preparing polysiloxane is shown in the figure numbers: 1-1-raw material tank; 1-2-first valve; 1-3-first temperature sensor; 1-4-first heating layer; 1-5-feeding port; 1-6-electric stirring mechanism; 1-7-feeding pump; 2-1 reactor; 2-2 filter screen; 2-3-baffle; 2-4-catalyst placement box; 2-5 second heating layer; 2-6-second temperature sensor; 2-7-second valve; 3-1 product tank; 3-2-third valve; 3-3-filter;
[0014] Figure 2 A top view of an assembleable catalyst cartridge;
[0015] Figure 3 An enlarged view of the assemblable catalyst cartridge. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0017] The first object of the present invention is to provide a solid acid catalyst and a preparation method thereof, which is suitable for preparing low molecular weight polysiloxane.
[0018] The second object of the present invention is to provide a device for preparing polysiloxane.
[0019] The third object of the present invention is to provide a method for preparing a target component in a low molecular weight polysiloxane.
[0020] The fourth object of the present invention is to provide a method for preparing high-resilience polyurethane foam.
[0021] The following is a detailed description of a solid acid catalyst and an apparatus and method for preparing polysiloxane using the solid acid catalyst provided in an embodiment of the present invention.
[0022] In a first aspect, an embodiment of the present invention provides a method for preparing a solid acid catalyst, which comprises: subjecting the acid-leached mesoporous zirconium phosphate powder to granulation and calcination, and then subjecting the acid-leaching to acid leaching again to obtain a solid acid catalyst.
[0023] The embodiment of the present invention provides a method for preparing a solid acid catalyst, based on the following characteristics of zirconium phosphate: zirconium phosphate is a new type of multifunctional mesoporous material and one of the layered solid acid materials. It has a large specific surface area and surface charge, is a strong solid acid, and has good ion exchange properties. Zirconium phosphate has the common properties of layered compounds and high chemical stability. It has both ion exchange properties like ion resins and shape-selective adsorption and catalytic properties like zeolites. It has high thermal stability and acid and alkali resistance. After acid leaching of the mesoporous zirconium phosphate powder, it can adsorb and carry part of the acid, and then granulate and roast it, which can improve the compressive strength and specific surface area of the molded material. After acid leaching again, it can adsorb and carry a large amount of acidic substances again, further enhancing the catalytic performance of the solid acid catalyst.
[0024] In some optional embodiments, the preparation method of the solid acid catalyst comprises: acid leaching and drying the mesoporous zirconium phosphate powder, mixing and extruding the powder with auxiliary materials, and then calcining the powder to obtain a calcined material; acid leaching and drying the calcined material again to obtain a solid acid catalyst;
[0025] Preferably, the method comprises the following steps: impregnating mesoporous zirconium phosphate powder in an acidic solution for the first time, and drying after the impregnation to obtain acidified mesoporous zirconium phosphate powder; uniformly mixing the acidified mesoporous zirconium phosphate powder with starch, sesbania powder, glycerol, glass fiber and water, and then extruding into particles, and calcining the obtained shaped particles to obtain a calcined material; impregnating the calcined material in an acidic solution for the second time, and drying after the impregnation to obtain a solid acid catalyst;
[0026] Preferably, during the first acid immersion, the weight ratio of the mesoporous zirconium phosphate powder to the acid solution is 1:10-1:20, and the acid used for the first immersion includes at least one of hydrochloric acid, sulfuric acid, carborane acid, and trifluoromethanesulfonic acid; the concentration of the acid solution is 50-100%; the immersion temperature is 25-35°C, and the time is 10-15h; the drying temperature is 60-140°C, and the time is 8-12h;
[0027] Preferably, the weight ratio of the mixture of the acidified mesoporous zirconium phosphate powder, starch, sesbania powder, glycerol, glass fiber and water is 100:1-10:1-20:1-20:1-20:1-50, the particle size of the formed particles obtained by extrusion is 50-100 mesh, and the formed particles are calcined at 400-700° C. for 1-5 hours to obtain a calcined material;
[0028] Preferably, during the second acid immersion, the weight ratio of the roasted material to the acid solution is 1:10-1:20, the acid used for the second immersion includes: at least one of hydrochloric acid, sulfuric acid, carborane acid, and trifluoromethanesulfonic acid; the concentration of the acid solution is 50-100%; the immersion temperature is 25-35° C., the time is 10-15 h; the drying temperature is 60-140° C., and the time is 8-12 h, to obtain a solid acid catalyst.
[0029] The embodiment of the present invention provides a preparation method of a solid acid catalyst, which comprises: impregnating mesoporous zirconium phosphate powder in an acidic solution for the first time, and drying after the impregnation to obtain acidified mesoporous zirconium phosphate powder; uniformly mixing the acidified mesoporous zirconium phosphate powder with starch, sesbania powder, glycerol, glass fiber and water, and then extruding into particles, and calcining the obtained molded particles to obtain a calcined material; and impregnating the calcined material in an acidic solution for a second time, and drying after the impregnation to obtain a solid acid catalyst. The above-mentioned preparation method, after acid leaching of mesoporous zirconium phosphate powder, can absorb and carry part of the acid, then mix it with starch, sesbania powder, glycerol, glass fiber and water and extrude it into particles, wherein: the aqueous solution of starch and sesbania powder has a certain viscosity, and has a better molding effect after mixing with the acidified zirconium phosphate powder, and can also be used as a filler before catalyst roasting, for catalyst pore expansion, glycerol as a lubricant to play a lubricating role, glass fiber can enhance the mechanical strength of the molded particles, after the above-mentioned auxiliary materials are mixed with the acidified mesoporous zirconium phosphate powder and then extruded through a molding machine, and then roasted, molded particles with good compressive strength and pore structure can be obtained, after the molded particles are acid-leached again, they can adsorb and carry a large amount of acidic substances in the pore structure, further enhancing the catalytic performance of the solid acid catalyst.
[0030] It can be seen that the embodiment of the present invention provides a method for preparing the above-mentioned solid acid catalyst. By using different zirconium sources and phosphorus sources to prepare zirconium phosphate solid powder, the obtained zirconium phosphate solid has a large specific surface area, and after granulation, a catalyst crude product is obtained. After subsequent calcination and impregnation, the catalyst can be activated and modified. Compared with conventional catalysts (such as sulfuric acid), the use of this catalyst does not require complicated post-processing work, does not generate solid waste, and is green and environmentally friendly.
[0031] In some optional embodiments, mesoporous zirconium phosphate powder is prepared by a hydrothermal method;
[0032] Preferably, the method comprises the following steps: uniformly mixing an aqueous solution of a phosphorus source and a zirconium source and a structure directing agent, adjusting the pH of the mixed solution, placing the mixed solution in a high-pressure sealed container for reaction, collecting the precipitate after the reaction is completed, washing, filtering and drying the precipitate, and then roasting and grinding to obtain a mesoporous zirconium phosphate solid powder;
[0033] Preferably, the phosphorus source includes at least one of phosphorous acid, hypophosphorous acid, and pyrophosphoric acid, the zirconium source includes at least one of zirconium chloride, zirconium nitrate, zirconium sulfate, zirconium butoxide, zirconium dioxide, and zirconium oxychloride, and the P / Zr molar ratio of the phosphorus source to the zirconium source is 0.3-1.3;
[0034] Preferably, the structure directing agent includes at least one of tetrapropylammonium hydroxide, ethylenediamine, n-butylamine, 1,8-octanediamine, F108, and P123, and the concentration of the structure directing agent in the mixed solution is 30-300 g / L; the mass ratio of the zirconium source to the structure directing agent is 0.1-1;
[0035] Preferably, the pH of the mixed solution is adjusted to 6-8 using aqueous ammonia;
[0036] Preferably, the hydrothermal reaction temperature is 150-200°C, the reaction pressure is 0.1-0.3Mpa, and the reaction time is 2-8h;
[0037] Preferably, washing comprises: washing the precipitate 3-5 times with deionized water, and the amount of water used for each washing is 10-20 times the mass of the precipitate, and the washing temperature is 20-40°C;
[0038] Preferably, the drying temperature is 50-80°C, the drying time is 36-72h, the roasting temperature is 300-400°C, and the roasting time is 2-6h.
[0039] By adding a structure directing agent in the above-mentioned preparation process, zirconium phosphate with a mesoporous structure can be synthesized, and the specific surface area of the zirconium phosphate can be further increased, so that the prepared mesoporous zirconium phosphate has good adsorption properties. Acid leaching can fully absorb the acid solution, increase the loading amount of the acid solution, and thereby improve the catalytic performance of the solid acid catalyst.
[0040] In the second aspect, an embodiment of the present invention provides an apparatus for preparing polysiloxane, which mainly includes: a raw material tank 1-1, a reaction tank 2-1 and a product tank 3-1, the raw material tank 1-1 is connected to the reaction tank 2-1, the reaction tank 2-1 is connected to the product tank 3-1, and a catalyst placement box 2-4 is provided in the reaction tank 2-1, and a solid acid catalyst prepared by the above-mentioned preparation method is placed in the catalyst placement box 2-4.
[0041] In some optional embodiments, a first valve 1-2 and a feed pump 1-7 are sequentially arranged between the discharge port of the raw material tank 1-1 and the feed port of the reaction tank 2-1, a second valve 2-7 is arranged between the discharge port of the reaction tank 2-1 and the feed port of the raw material tank 1-1, and a third valve 3-2 and a filter 3-3 are sequentially arranged between the discharge port of the reaction tank 2-1 and the feed port of the product tank 3-1.
[0042] In some optional embodiments, a plurality of alternately arranged baffles 2-3 are provided in the reaction tank 2-1, and the baffles 2-3 are provided with upper and lower layers of support nets for fixing and supporting the catalyst placement box 2-4;
[0043] Preferably, a catalyst placement box 2-4 is detachably mounted on the baffle 2-3 in the reaction tank 2-1;
[0044] Preferably, the catalyst placement box 2-4 is in the shape of a rectangle with one side being an arc; the length of the catalyst placement box 2-4 is 1 / 2-2 / 3 of the diameter of the reaction tank 2-1, the width is 1 / 4-1 / 3 of the diameter of the reaction tank 2-1, and the height is 1 / 10-1 / 5 of the diameter of the reaction tank 2-1;
[0045] Preferably, two adjacent layers of catalyst placement boxes 2-4 are placed parallel and opposite to each other on each layer;
[0046] Preferably, the catalyst placement box 2-4 is filled with catalyst and filler A, and the particle size of filler A is 50-100 mm;
[0047] Preferably, a filler B is placed between two adjacent layers of catalyst placement boxes 2-4, and the particle size of the filler B is 5-30 mm;
[0048] Preferably, a filter screen 2-2 is provided at the bottom of the reaction tank 2-1, a second heating layer 2-5 is provided on the outer wall, and a second temperature sensor 2-6 is provided inside the reaction tank 2-1.
[0049] In some optional embodiments, an electric stirring mechanism 1-6 and a first temperature sensor 1-3 are provided in the raw material tank 1-1, and a first heating layer 1-4 is provided on the outer wall.
[0050] The present invention provides a device for preparing polysiloxane. The device can be used to prepare polysiloxane, which can more effectively improve the reaction efficiency. The product can be separated into solid and liquid without further processing, thereby achieving a green and environmentally friendly effect.
[0051] In a third aspect, an embodiment of the present invention also provides a method for preparing polysiloxane using the above-mentioned device, comprising the following steps: adding reaction raw materials into a raw material tank 1-1, and loading the prepared solid acid catalyst into a catalyst placement box 2-4 and then filling it into a reaction tank 2-1, and introducing the reaction raw materials in the raw material tank 1-1 into the reaction tank 2-1 for reaction.
[0052] In some optional embodiments, the steps include: adding the reaction raw materials into the raw material tank 1-1, and loading the prepared solid acid catalyst into the catalyst placement box 2-4 and then filling it into the reaction tank 2-1, turning on the stirring and heating in the raw material tank 1-1, mixing the reaction raw materials evenly and heating them to a preset temperature, opening the first valve 1-2 and starting the feed pump 1-7 to allow the reaction raw materials to be filtered through the filter screen 2-2 and then enter the reaction tank 2-1 for reaction;
[0053] Preferably, the reaction raw materials in the raw material tank 1-1 include: polydimethylcyclosiloxane and hexamethyldisiloxane end-capping agent, and the structure of polydimethylsiloxane is MD m M, m=5-10; M: -Si(CH3)3, D: -Si(CH3)2-O-;
[0054] Preferably, a solid acid catalyst and filler A are placed in the catalyst placement box 2-4 in the reaction tank 2-1, and filler B is placed between two adjacent layers of catalyst placement boxes 2-4;
[0055] Preferably, the ratio of solid acid catalyst to filler A is 1:2-1:10;
[0056] Preferably, filler A includes one or more of molecular sieves, polymer microspheres, quartz sand, activated alumina balls, and polytetrafluoroethylene balls;
[0057] Preferably, the filler B comprises zeolite, ceramic balls, stainless steel Raschig rings, stainless steel Pall rings, and stainless steel step rings;
[0058] Preferably, the stirring speed in the raw material tank 1-1 is 300-600r / min;
[0059] Preferably, the feed flow rate of feed pump 1-7 is 500-1500 mL / min;
[0060] Preferably, the reaction temperature in the reaction tank 2-1 is 30-60°C;
[0061] Preferably, the process further includes: after the reaction of the reaction raw materials in the reaction tank 2-1 is completed, the second valve 2-7 is opened to circulate the reaction products back into the raw material tank 1-1, and each time the gas phase data is sampled and tested to detect the target component content, and when the target component content remains stable, the third valve 3-2 is opened, and after filtering through the filter 3-3, the material is discharged to the product tank 3-1.
[0062] In a fourth aspect, an embodiment of the present invention further provides a method for preparing a high-resilience polyurethane foam, comprising: preparing a high-resilience polyurethane foam by compounding a surfactant obtained by using the polysiloxane prepared by the above preparation method and a polyether.
[0063] The present invention provides a preparation method for increasing the target component in low molecular weight polysiloxane. The solid acid catalyst and device prepared herein can effectively increase the content of the target component, and the prepared low molecular weight polysiloxane can effectively increase the open cell rate of high resilience foam.
[0064] The present invention will be further described below in conjunction with the embodiments.
[0065] A device for preparing polysiloxane, see Figure 1 , mainly including: a raw material tank 1-1, a reaction tank 2-1 and a product tank 3-1, the raw material tank 1-1 is connected with the reaction tank 2-1, the reaction tank 2-1 is connected with the product tank 3-1, a first valve 1-2 and a feed pump 1-7 are arranged in sequence between the discharge port of the raw material tank 1-1 and the feed port of the reaction tank 2-1, a second valve 2-7 is arranged between the discharge port of the reaction tank 2-1 and the feed port of the raw material tank 1-1, and a third valve 3-2 and a filter 3-3 are arranged in sequence between the discharge port of the reaction tank 2-1 and the feed port of the product tank 3-1.
[0066] A first temperature sensor 1-3 and an electric stirring mechanism 1-6 are arranged in the raw material tank 1-1, a feeding port 1-5 is arranged at the top, and a first heating layer 1-4 is arranged on the outer wall.
[0067] See also Figure 2 and Figure 3, a filter screen 2-2 is provided at the bottom of the reaction tank 2-1, a second heating layer 2-5 is provided on the outer wall, a second temperature sensor 2-6 is provided inside the reaction tank 2-1, a catalyst placement box 2-4 is provided inside the reaction tank 2-1, and the solid acid catalyst prepared by the present invention is placed in the catalyst placement box 2-4. A plurality of alternately arranged baffles 2-3 are provided inside the reaction tank 2-1, and the baffles 2-3 are provided with upper and lower layers of support nets for fixing and supporting the catalyst placement box 2-4; the catalyst placement box 2-4 is detachably mounted on the baffles 2-3 inside the reaction tank 2-1, and the shape of the catalyst placement box 2-4 is a rectangle with one side being curved; the length of the catalyst placement box 2-4 is 1 / 2-2 / 3 of the diameter of the reaction tank 2-1, the width is 1 / 4-1 / 3 of the diameter of the reaction tank 2-1, and the height is the diameter of the reaction tank 2-1 1 / 10-1 / 5 of the total weight; two adjacent layers of catalyst placement boxes 2-4 are placed parallel to each other in each layer; the catalyst placement box 2-4 is filled with catalyst and filler A, and the particle size of filler A is 50-100; the ratio of solid acid catalyst to filler A is 1:2-1:10; filler A includes one or more of molecular sieves, polymer microspheres, quartz sand, activated alumina balls, and polytetrafluoroethylene balls; filler B is placed between two adjacent layers of catalyst placement boxes 2-4, and the particle size of filler B is 5-30mm.
[0068] The method for preparing polysiloxane using the above-mentioned device comprises the following steps: adding the reaction raw materials into the raw material tank 1-1 from the feeding port 1-5, and loading the prepared solid acid catalyst into the catalyst placement box 2-4 and then filling it into the reaction tank 2-1, stirring and heating the reaction raw materials by using the electric stirring mechanism 1-6 and the first heating layer 1-4 in the raw material tank 1-1, monitoring the temperature of the reaction raw materials by using the first temperature sensor 1-3 until the temperature reaches a preset temperature, opening the first valve 1-2 and starting the feed pump 1-7 to filter the reaction raw materials through the filter screen 2-2, and then entering The reaction tank 2-1, the reaction raw materials react under the heating of the second heating layer 2-5 and the catalytic action of the solid acid catalyst in the catalyst placement box 2-3, and the reaction temperature in the reaction tank 2-1 is monitored by the second temperature sensor 2-6 during the reaction. After one reaction is completed, the second valve 2-7 is opened to circulate the reaction product back to the raw material tank 1-1. After each cycle, the gas phase data is sampled and tested to detect the target component content. When the component content remains stable, the third valve 3-2 is opened, and after filtering through the filter 3-3, the material is discharged to the product tank 3-1, wherein:
[0069] The reaction raw materials in the raw material tank 1-1 include: polydimethylcyclosiloxane and hexamethyldisiloxane end-capping agent, the structure of polydimethylsiloxane is MD mM, m=5-10; M: -Si(CH3)3, D: -Si(CH3)2-O-; the stirring speed in the raw material tank 1-1 is 300-600r / min; the feed flow rate of the feed pump 1-7 is 500-1500mL / min; the reaction temperature in the reaction tank 2-1 is 30-60℃.
[0070] Example 1
[0071] (1) 20 g of phosphorous acid and 70 g of zirconium chloride were prepared into 200 g of aqueous solution, and then 200 mL of 100 g / L ethylenediamine aqueous solution was added and stirred evenly, and ammonia water was added to adjust the pH value of the solution to 6.0; then the mixed solution was transferred to a high-pressure reactor, and reacted at 180°C and 0.1 MPa for 5 h, and then the solid precipitate was filtered and collected to obtain 35 g of solid precipitate, and the precipitate was washed 3 times with deionized water at 30°C, and the amount of deionized water used each time was 400 g; then it was dried at 60°C for 40 h. After drying, the dried material was roasted at 350°C for 4 h, and then ground to obtain a solid powder.
[0072] (2) The solid powder was immersed in 98% sulfuric acid at a solid-liquid weight ratio of 1:12 at 25°C for 10 hours, drained, and dried at 150°C. The acidified solid powder was blended with starch, sesbania powder, glycerol, glass fiber, and water in a ratio of 100:5:10:10:10:30, stirred at 50°C for 30 minutes, and then extruded into 50-mesh particles using a molding machine. The formed particles were placed in an oven and roasted at 400°C for 3 hours.
[0073] (3) Add the solid acid particles to 98% sulfuric acid at a solid-liquid weight ratio of 1:10 and soak at 25°C for 8 hours; then drain the liquid from the solid particles and place them in an oven, dry them at 100°C for 5 hours, and take them out to obtain solid catalyst A.
[0074] Example 2
[0075] (1) 8g of phosphorous acid, 7g of hypophosphorous acid, 18g of zirconium chloride and 25g of zirconium chloride oxide were prepared into 200g of aqueous solution, and then 280mL of 150g / L P123 aqueous solution was added and stirred evenly, and ammonia water was added to adjust the pH value of the solution to 8.0; then the mixed solution was transferred to a high-pressure reactor, reacted at 200°C and 0.2Mpa for 6h, and then the solid precipitate was filtered and collected to obtain 30g of solid precipitate, and the precipitate was washed twice with deionized water at 30°C, and the amount of deionized water used each time was 550g; then it was dried at 70°C for 35h. After drying, the dried material was roasted at 350°C for 4h, and then ground to obtain solid powder.
[0076] (2) The solid powder was immersed in 100% trifluoromethanesulfonic acid at a solid-liquid weight ratio of 1:15 at 25°C for 9 hours, and then dried at 160°C after being drained. The acidified solid powder was blended with starch, sesbania powder, glycerol, glass fiber, and water at a ratio of 100:6:10:12:10:35, and after being stirred at 60°C for 35 minutes, it was extruded into 80 mesh particles using a molding machine. The formed particles were placed in an oven and roasted at 400°C for 3 hours.
[0077] (3) placing the solid particles in 98% trifluoromethanesulfonic acid at a solid-liquid weight ratio of 1:15 and soaking them at 25°C for 6 hours; then draining the liquid from the solid particles and placing them in an oven, drying them at 100°C for 4 hours, and taking them out to obtain solid catalyst B.
[0078] Example 3
[0079] According to the MD6M structure, polysiloxane synthesis is carried out, 36.63kg of octamethylcyclotetrasiloxane and 13.37kg of hexamethyldisiloxane are added to the raw material tank 1-1 and stirred and mixed, and then 1.00kg of the solid acid catalyst A prepared in Example 1 is mixed with 8.00kg of 4A molecular sieve, and the mixture is added to the assembleable catalyst box, and then the catalyst box is placed in the reaction tank 2-1, and the stainless steel Raschig ring with a particle size of 10mm is filled with the entire reaction tank 2-1. The stirring and heating in the raw material tank 1-1 are turned on. When the material temperature reaches 50°C, the feed pump 1-7 is turned on, and the feed flow rate is controlled to be 1000mL / min to make the mixed material pass through the 50°C reaction tank 2-1, return to the raw material tank 1-1, and recycle. After each cycle, the gas phase is sampled and tested to detect the content of the target component. After 6 cycles, the target component content is detected to remain stable and the material is discharged.
[0080] Example 4
[0081] According to the MD6M structure, polysiloxane synthesis was performed, 36.63kg of octamethylcyclotetrasiloxane and 13.37kg of hexamethyldisiloxane were added to the raw material tank 1-1 and stirred and mixed, and then 1.00kg of the solid acid catalyst A prepared in Example 2 was mixed with 8.00kg of 4A molecular sieves, and the mixture was added to the assembleable catalyst box, and then the catalyst box was placed in the reaction tank 2-1, and the stainless steel Raschig ring with a particle size of 10mm was filled with the entire reaction tank 2-1. The stirring and heating in the raw material tank 1-1 were turned on, and when the material temperature reached 50°C, the feed pump 1-7 was turned on, and the feed flow rate was controlled to be 1000mL / min to make the mixed material pass through the 40°C reaction tank 2-1, return to the raw material tank 1-1, and recirculate, and each cycle was sampled and tested for gas phase, and the target component content was detected. After 5 cycles, the target component content was detected to remain stable and the material was discharged.
[0082] Example 5
[0083] According to the MD6M structure, polysiloxane synthesis was performed, 36.63kg of octamethylcyclotetrasiloxane and 13.37kg of hexamethyldisiloxane were added to the raw material tank 1-1 and stirred and mixed, and then 2.00kg of the solid acid catalyst B prepared in Example 2 was mixed with 5.00kg of 4A molecular sieve, and the mixture was added to the assembleable catalyst box, and then the catalyst box was placed in the reaction tank 2-1, and the stainless steel Raschig ring with a particle size of 15mm was filled with the entire reaction tank 2-1. The stirring and heating in the raw material tank 1-1 were turned on, and when the material temperature reached 40°C, the feed pump 1-7 was turned on, and the feed flow rate was controlled to be 1200mL / min to make the mixed material pass through the 60°C reaction tank 2-1, return to the raw material tank 1-1, and recirculate, and each cycle was sampled and tested for gas phase, and the target component content was detected. After 2 cycles, the target component content was detected to remain stable and the material was discharged.
[0084] Example 6
[0085] According to the MD8M structure, polysiloxane synthesis was performed. 39.26 kg of octamethylcyclotetrasiloxane and 10.74 kg of hexamethyldisiloxane were added to the raw material tank 1-1 and stirred and mixed. Then 1.50 kg of the solid acid catalyst B prepared in Example 2 was mixed evenly with 5.00 kg of 4A molecular sieve. The mixture was added to the assembleable catalyst box, and the catalyst box was placed in the reaction tank 2-1. In addition, the stainless steel ball ring with a particle size of 25 mm was filled with the entire reaction tank 2-1. The stirring and heating in the raw material tank 1-1 were turned on. When the material temperature reached 45 ° C, the feed pump 1-7 was turned on, and the feed flow rate was controlled to be 1000 mL / min to make the mixed material pass through the 45 ° C reaction tank 2-1, return to the raw material tank 1-1, and re-circulate. After each cycle, the gas phase was sampled and tested to detect the content of the target component. After 3 cycles, the target component content was detected to remain stable and the material was discharged.
[0086] Example 7
[0087] According to the MD9M structure, polysiloxane synthesis was performed. 40.22 kg of octamethylcyclotetrasiloxane and 9.78 kg of hexamethyldisiloxane were added to the raw material tank 1-1 and stirred and mixed. Then 1.20 kg of the solid acid catalyst B prepared in Example 1 was mixed evenly with 5.00 kg of 4A molecular sieve. The mixture was added to the assembleable catalyst box, and the catalyst box was placed in the reaction tank 2-1. In addition, the stainless steel ball ring with a particle size of 20 mm was filled with the entire reaction tank 2-1. The stirring and heating in the raw material tank 1-1 were turned on. When the material temperature reached 45 ° C, the feed pump 1-7 was turned on, and the feed flow rate was controlled to be 1000 mL / min to make the mixed material pass through the 45 ° C reaction tank 2-1, return to the raw material tank 1-1, and re-circulate. After each cycle, the gas phase was sampled and tested to detect the content of the target component. After 4 cycles, the target component content was detected to remain stable and the material was discharged.
[0088] Example 8
[0089] By MD 10 M structure for polysiloxane synthesis, octamethylcyclotetrasiloxane 41.02kg, hexamethyldisiloxane 8.98kg added to the raw material tank 1-1 and opened to stir and mix, then 2.00kg of the solid acid catalyst B prepared in Example 2 and 5.00kg of 4A molecular sieve were mixed evenly, the mixture was added to the assembleable catalyst box, and then the catalyst box was placed in the reaction tank 2-1, and the ceramic balls with a particle size of 20mm were filled with the entire reaction tank 2-1. The stirring and heating in the raw material tank 1-1 were turned on, and when the material temperature reached 40°C, the feed pump 1-7 was turned on, and the feed flow rate was controlled to be 1200mL / min to make the mixed material pass through the 60°C reaction tank 2-1, return to the raw material tank 1-1, and re-circulate, each cycle, sample the gas phase, detect the target component content, and detect the target component content after 3 cycles to keep stable, and discharge.
[0090] Comparative Example 1
[0091] According to the MD6M structure, polysiloxane was synthesized, 36.63 kg of octamethylcyclotetrasiloxane and 13.37 kg of hexamethyldisiloxane were put into the reactor, and 6.00 kg of white clay was added into the reactor. The stirring and heating in the raw material tank 1-1 were turned on. When the material temperature reached 80°C, insulation was started. The gas phase was sampled and tested every hour to detect the content of the target component. When the insulation time reached 4 hours, the content of the target component remained stable and the material was discharged.
[0092] Comparative Example 2
[0093] According to the MD6M structure, polysiloxane was synthesized, 36.63 kg of octamethylcyclotetrasiloxane and 13.37 kg of hexamethyldisiloxane were put into the reactor, and then 4.00 kg of sulfuric acid was added to the reactor. The stirring and heating in the raw material tank 1-1 were turned on. When the material temperature reached 60°C, it was kept warm for a period of time. The gas phase was sampled and tested every hour to detect the content of the target component. When the holding time reached 6 hours, the content of the target component remained stable. 24.00 kg of sodium bicarbonate was added to neutralize for 4 hours and the material was filtered out.
[0094] Comparative Example 3
[0095] According to the MD6M structure, polysiloxane was synthesized, 36.63 kg of octamethylcyclotetrasiloxane and 13.37 kg of hexamethyldisiloxane were put into the reactor, and then 8.00 kg of cationic ion exchange resin was added to the reactor. The stirring and heating in the raw material tank 1-1 were turned on. When the material temperature reached 60°C, insulation was started. The gas phase was sampled and tested every hour to detect the content of the target component. When the insulation time reached 4 hours, the content of the target component remained stable and the material was discharged.
[0096] Comparative Example 4
[0097] According to the MD8M structure, polysiloxane was synthesized, 39.26 kg of octamethylcyclotetrasiloxane and 10.74 kg of hexamethyldisiloxane were put into the reactor, and 6.00 kg of white clay was added to the reactor. The stirring and heating in the raw material tank 1-1 were turned on. When the material temperature reached 80°C, insulation was started. The gas phase was sampled and tested every hour to detect the content of the target component. When the insulation time reached 4 hours, the content of the target component remained stable and the material was discharged.
[0098] Comparative Example 5
[0099] According to the MD9M structure, polysiloxane was synthesized, 40.22 kg of octamethylcyclotetrasiloxane and 9.78 kg of hexamethyldisiloxane were put into the reactor, and then 4.00 kg of sulfuric acid was added to the reactor. The stirring and heating in the raw material tank 1-1 were turned on. When the material temperature reached 60°C, it was kept warm for a period of time. The gas phase was sampled and tested every hour to detect the content of the target component. When the holding time reached 6 hours, the content of the target component remained stable. 24.00 kg of sodium bicarbonate was added to neutralize for 4 hours and the material was filtered out.
[0100] Comparative Example 6
[0101] By MD 10M structure for polysiloxane synthesis, 41.02kg of octamethylcyclotetrasiloxane and 8.98kg of hexamethyldisiloxane are put into the reactor, and then 8.00kg of cationic ion exchange resin is added into the reactor. Turn on the stirring and heating in the raw material tank 1-1, when the material temperature reaches 60°C, keep it warm for a period of time, sample and test the gas phase every hour, detect the content of the target component, when the insulation time reaches 6h, the content of the target component remains stable, and the material is discharged.
[0102] Comparative Example 7
[0103] According to the MD6M structure, polysiloxane synthesis was performed, 36.63 kg of octamethylcyclotetrasiloxane and 13.37 kg of hexamethyldisiloxane were added to the raw material tank 1-1 and stirred and mixed, and then 1.00 kg of solid acid catalyst C (similar to the steps in Example 1, except that the structure-directing agent ethylenediamine was not added during the preparation of zirconium phosphate, and the other steps remained unchanged) was mixed evenly with 8.00 kg of 4A molecular sieve, and the mixture was added to the assembleable catalyst box, and then the catalyst box was placed in the reaction tank 2-1, and the stainless steel Raschig ring with a particle size of 10 mm was filled with the entire reaction tank 2-1. The stirring and heating in the raw material tank 1-1 were turned on, and when the material temperature reached 50 ° C, the feed pump 1-7 was turned on, and the feed flow rate was controlled to be 1000 mL / min to make the mixed material pass through the 50 ° C reaction tank 2-1, return to the raw material tank 1-1, and re-circulate, and each cycle was sampled and tested for gas phase, and the target component content was detected. After 10 cycles, the target component content was detected to remain stable and the material was discharged.
[0104] Comparative Example 8
[0105] The steps are similar to those in Example 3, except that filler A is not added to the catalyst box, filler B is not added to the reaction tank, and other conditions remain unchanged.
[0106] The following Table 1 shows the component contents of Examples 3-8 and Comparative Examples 1-8.
[0107] Table 1
[0108]
[0109]
[0110] Based on the analysis results of the MD6M polydimethylsiloxane components prepared in Examples 3-5 and Comparative Examples 1-3, and compared with catalysts such as clay, sulfuric acid, and cationic ion exchange resin, the solid catalyst, device, and process prepared by the present invention can effectively increase the content of the target component.
[0111] Based on the analysis results of the polydimethylsiloxane components with different structures prepared in Examples 6-8 and Comparative Examples 4-6, and by comparing kaolin, sulfuric acid, and cationic ion exchange resin catalyst (manufacturer: Jiangyin Nanda Synthetic Chemical Co., Ltd., resin model: amberlyst15), the solid catalyst, device and process prepared by the present invention can effectively increase the content of the target component.
[0112] In summary, the low molecular weight polydimethylsiloxane prepared by the catalyst and device provided in this article can effectively improve MD m M, m = 5-10 component content, and can reduce the ring content.
[0113] The polysiloxane and polyether obtained in the above Examples 3-5 and Comparative Examples 1-3 are compounded and used as surfactants to prepare polyurethane high-resilience polyurethane foam. Specifically, the high-resilience polyurethane foam is prepared by reacting component X and component Y. The preparation method is as follows:
[0114] Preparation of component X: According to the formula in Table 2, the weighed polyol, catalyst, foaming agent and surfactant are mixed and stirred at room temperature for 20 seconds.
[0115] The following Table 3 is an evaluation of the formulations in Table 2.
[0116] Table 2
[0117] raw material formula ZSN-330 70 GP104 30 Surfactants 1.0 A1 0.1 A33 0.4 DEOA 1 Stannous Octoate 0.4 water 4
[0118] The Y component material is TM20, which refers to a mixture of TDI (toluene diisocyanate) and MDI (diphenylmethane diisocyanate), wherein TDI accounts for 80% and MDI accounts for 20%.
[0119] When in use, mix the X and Y components in a weight ratio of X:Y=100:35, stir for 5s at 2000r / min, and pour into a standard mold (mold temperature 25°C) without free foaming. The foam will be made into high-resilience polyurethane foam after rising, growing and maturing, and data testing will be carried out on the FOAMAT285 instrument at the same time. The standard square mold exhaust force test method refers to: "GBT10807-2006 Determination of hardness of soft foam polymer materials (indentation method)"; other test methods refer to: "QBT2080-2010 High-resilience soft polyurethane foam plastics".
[0120] Table 3 below shows the test results of the standard square mold exhaust force of the foam corresponding to the embodiments and comparative examples.
[0121] Table 3
[0122]
[0123]
[0124] Based on the foam test results, compared with polydimethylsiloxane prepared by white clay, sulfuric acid, and cationic ion exchange resin processes, when the polydimethylsiloxane prepared by the present invention is used to prepare high-resilience polyurethane foam, the stress release force of the foam is significantly reduced, the rebound rate and the air permeability are greatly improved, and the opening performance of the foam is significantly improved.
[0125] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a solid acid catalyst, characterized in that: It includes: The mesoporous zirconium phosphate powder after acid leaching is granulated and calcined, and then acid leached again to obtain a solid acid catalyst.
2. The preparation method according to claim 1, characterized in that: The preparation method of the solid acid catalyst comprises: acid leaching and drying the mesoporous zirconium phosphate powder, mixing and extruding the powder with auxiliary materials, and then calcining the powder to obtain a calcined material; acid leaching and drying the calcined material again to obtain a solid acid catalyst; Preferably, the method comprises the following steps: impregnating mesoporous zirconium phosphate powder in an acidic solution for the first time, and drying after the impregnation to obtain acidified mesoporous zirconium phosphate powder; uniformly mixing the acidified mesoporous zirconium phosphate powder with starch, sesbania powder, glycerol, glass fiber and water, and then extruding into particles, and calcining the obtained shaped particles to obtain a calcined material; impregnating the calcined material in an acidic solution for the second time, and drying after the impregnation to obtain a solid acid catalyst; Preferably, during the first acid immersion, the weight ratio of the mesoporous zirconium phosphate powder to the acid solution is 1:10-1:20, and the acid used for the first immersion includes at least one of hydrochloric acid, sulfuric acid, carborane acid, and trifluoromethanesulfonic acid; the concentration of the acid solution is 50-100%; the immersion temperature is 25-35°C, and the time is 10-15h; the drying temperature is 60-140°C, and the time is 8-12h; Preferably, the weight ratio of the acidified mesoporous zirconium phosphate powder to starch, sesbania powder, glycerol, glass fiber and water is 100:1-10:1-20:1-20:1-20:1-50, the particle size of the formed particles obtained by extrusion is 50-100 mesh, and the formed particles are calcined at 400-700°C for 1-5h to obtain a calcined material; Preferably, during the second acid immersion, the weight ratio of the roasted material to the acid solution is 1:10-1:20, the acid used for the second immersion includes: at least one of hydrochloric acid, sulfuric acid, carborane acid, and trifluoromethanesulfonic acid; the concentration of the acid solution is 50-100%; the immersion temperature is 25-35°C, the time is 10-15h; the drying temperature is 60-140°C, and the time is 8-12h, to obtain a solid acid catalyst.
3. The preparation method according to claim 1 or 2, characterized in that: Mesoporous zirconium phosphate powder was prepared by hydrothermal method. Preferably, the method comprises the following steps: uniformly mixing an aqueous solution of a phosphorus source and a zirconium source and a structure directing agent, adjusting the pH of the mixed solution, placing the mixed solution in a high-pressure sealed container for reaction, collecting the precipitate after the reaction is completed, washing, filtering and drying the precipitate, and then roasting and grinding to obtain a mesoporous zirconium phosphate solid powder; Preferably, the phosphorus source includes at least one of phosphorous acid, hypophosphorous acid, and pyrophosphoric acid, the zirconium source includes at least one of zirconium chloride, zirconium nitrate, zirconium sulfate, zirconium butoxide, zirconium dioxide, and zirconium oxychloride, and the P / Zr molar ratio of the phosphorus source to the zirconium source is 0.3-1.3; Preferably, the structure directing agent includes at least one of tetrapropylammonium hydroxide, ethylenediamine, n-butylamine, 1,8-octanediamine, F108, and P123, and the concentration of the structure directing agent in the mixed solution is 30-300 g / L; the mass ratio of the zirconium source to the structure directing agent is 0.1-1; Preferably, the pH of the mixed solution is adjusted to 6-8 using aqueous ammonia; Preferably, the temperature of the hydrothermal reaction is 150-200°C, the reaction pressure is 0.1-0.3Mpa, and the reaction time is 2-8h; Preferably, the water washing comprises: washing the precipitate 3-5 times with deionized water, and the amount of water used for each washing is 10-20 times the mass of the precipitate, and the washing temperature is 20-40°C; Preferably, the drying temperature is 50-80°C, the drying time is 36-72h, the roasting temperature is 300-400°C, and the roasting time is 2-6h.
4. A device for preparing polysiloxane, characterized in that: Mainly includes: Raw material tank (1-1), a reaction tank (2-1) and a product tank (3-1), the raw material tank (1-1) is connected to the reaction tank (2-1), the reaction tank (2-1) is connected to the product tank (3-1), and a catalyst placement box (2-4) is arranged in the reaction tank (2-1), and a solid acid catalyst prepared by the preparation method according to any one of claims 1 to 3 is placed in the catalyst placement box (2-4).
5. The device according to claim 4, characterized in that The raw material tank (1-1) is provided with a first temperature sensor (1-3) and an electric stirring mechanism (1-6), a feed port (1-5) is provided at the top, and a first heating layer (1-4) is provided on the outer wall.
6. The device according to claim 4, characterized in that A plurality of alternately arranged baffles (2-3) are arranged in the reaction tank (2-1), and the baffles (2-3) are provided with upper and lower layers of support nets for fixing and supporting the catalyst placement box (2-4); Preferably, a catalyst placement box (2-4) is detachably mounted on the baffle (2-3) in the reaction tank (2-1); Preferably, the shape of the catalyst placement box (2-4) is a rectangle with one side being curved; the length of the catalyst placement box (2-4) is 1 / 2-2 / 3 of the diameter of the reaction tank (2-1), the width is 1 / 4-1 / 3 of the diameter of the reaction tank (2-1), and the height is 1 / 10-1 / 5 of the diameter of the reaction tank (2-1); Preferably, two adjacent layers of catalyst placement boxes (2-4) are placed parallel to each other on each layer; Preferably, the catalyst placement box (2-4) contains a catalyst and a filler A, and the particle size of the filler A is 50-100 mm; Preferably, a filler B is placed between two adjacent layers of catalyst placement boxes (2-4), and the particle size of the filler B is 5-30 mm; Preferably, a filter screen (2-2) is provided at the bottom of the reaction tank (2-1), a second heating layer (2-5) is provided on the outer wall, and a second temperature sensor (2-6) is provided inside the reaction tank (2-1).
7. The device according to claim 4, characterized in that A first valve (1-2) and a feed pump (1-7) are arranged in sequence between the discharge port of the raw material tank (1-1) and the feed port of the reaction tank (2-1), a second valve (2-7) is arranged between the discharge port of the reaction tank (2-1) and the feed port of the raw material tank (1-1), and a third valve (3-2) and a filter (3-3) are arranged in sequence between the discharge port of the reaction tank (2-1) and the feed port of the product tank (3-1).
8. A method for preparing polysiloxane using the device according to any one of claims 4 to 7, characterized in that: The following steps are involved: The reaction raw materials are added into the raw material tank (1-1), and the prepared solid acid catalyst is loaded into the catalyst placement box (2-4) and then filled into the reaction tank (2-1), and the reaction raw materials in the raw material tank (1-1) are introduced into the reaction tank (2-1) for reaction.
9. The method according to claim 8, characterized in that The following steps are involved: Adding reaction raw materials into a raw material tank (1-1), and placing the prepared solid acid catalyst into a catalyst placement box (2-4) and then filling it into a reaction tank (2-1), turning on the stirring and heating in the raw material tank (1-1), mixing the reaction raw materials uniformly and heating them to a preset temperature, opening the first valve (1-2) and starting the feed pump (1-7) to allow the reaction raw materials to be filtered through a filter screen (2-2) and then enter the reaction tank (2-1) for reaction; Preferably, the reaction raw materials in the raw material tank (1-1) include: polydimethylcyclosiloxane and hexamethyldisiloxane end-capping agent, and the structure of the polydimethylsiloxane is MD m M, m=5-10; M: -Si(CH3)3, D: -Si(CH3)2-O-; Preferably, a solid acid catalyst and filler A are placed in the catalyst placement box (2-4) in the reaction tank (2-1), and filler B is placed between two adjacent layers of catalyst placement boxes (2-4); Preferably, the ratio of the solid acid catalyst to the filler A is 1:2-1:10; Preferably, the filler A includes one or more of molecular sieves, polymer microspheres, quartz sand, activated alumina balls, and polytetrafluoroethylene balls; Preferably, the filler B comprises zeolite, ceramic balls, stainless steel Raschig rings, stainless steel Pall rings, and stainless steel step rings; Preferably, the stirring speed in the raw material tank (1-1) is 300-600 r / min; Preferably, the feed flow rate of the feed pump (1-7) is 500-1500 mL / min; Preferably, the reaction temperature in the reaction tank (2-1) is 30-60°C; Preferably, the method further comprises: after the reaction of the reaction raw materials in the reaction tank (2-1) is completed, opening the second valve (2-7) to allow the reaction product to circulate back into the raw material tank (1-1); after each circulation, sampling and testing the gas phase data, detecting the target component content, and when the target component content remains stable, opening the third valve (3-2), filtering through the filter (3-3), and discharging the material into the product tank (3-1).
10. A method for preparing a high-resilience polyurethane foam, characterized in that: It includes: A surfactant obtained by compounding polysiloxane prepared by the preparation method according to any one of claims 8 to 9 with polyether is used to prepare high-resilience polyurethane foam.